Variation in Branching Pattern of Splenic Artery- A Cadaveric Study - T Sadeesh; G Prabavathy (Academia Anatomica International, 2020)
Background: Splenic artery is the largest branch of the celiac trunk in adults and is the second-largest next to the common hepatic artery in fetal life. The present study was conducted to assess variation in the branching pattern of the splenic artery. Subjects and Methods: The present cadaveric study was conducted on 54 cadavers embalmed with 10% formalin. The peritoneal cavity was opened and explored. The celiac trunk, splenic artery and its branches were noted and photographed. Results: out of 54 cadavers, 26 were males and 28 were males. The origin of the splenic artery was from the celiac trunk in 47, a superior mesenteric artery in 4 and abdominal aorta in 3 cases. The difference was significant (P< 0.05). Conclusion: Authors found that surgeons should have a thorough knowledge regarding the branching pattern of the splenic artery. There was variation in the origin of the splenic artery such as from celiac trunk, superior mesenteric artery and abdominal aorta.